Association of HER2-low with clinicopathological features in patients with early invasive lobular breast cancer: an international multicentric study - Karen Van Baelen; Ha-Linh Nguyen; François Richard; Gitte Zels; Maria Margarete Karsten; Guilherme Nader-Marta; Peter Vermeulen; Luc Dirix; Adam David Dordevic; Evandro de Azambuja; Denis Larsimont; Marion Maetens; et al. (Breast Cancer Research)
Abstract Purpose The antibody–drug conjugate trastuzumab deruxtecan has proven to be not only efficient in patients with HER2+ breast cancers (BC), but also in those patients with so-called HER2-low BC. HER2-low tumors are well described in the general BC population, but not in patients with invasive lobular carcinoma (ILC). Here, we aimed at analyzing the association of HER2-low with clinicopathological features and survival outcomes in patients with early-stage pure ILC. Methods A multicentric retrospective cohort of patients diagnosed with stage I-III estrogen receptor positive (ER+) HER2 negative (HER2-) ILC between 01/01/2000 and 12/31/2020 was assembled. HER2- disease was categorized further by immunohistochemical (IHC) score into HER2 0, HER2 1+ and HER2 2+ following time appropriate ASCO/CAP guidelines from 2007 onward and by local guidelines prior to 2007. The association of HER2-low (HER2 1+ and 2+) with clinicopathological variables was assessed using multinomial logistic regression. Survival analyses were performed to evaluate the association of HER2-low with disease-free (DFS), distant recurrence-free (DRFS) and overall survival (OS). Results The data of 2098 patients with ER+ HER2- ILC was collected of which 1103 (52.6%) had a HER2-low tumor. Of these 716 (34.1%) had an IHC score of HER2 1+ and 387 (18.4%) of HER2 2+. In multivariable analysis, both tumor size of ≥ 2cm (OR: 1.37; 95%CI 1.01 – 1.87; p-value 0.042) and multifocality (OR: 1.55; 95%CI 1.11 – 2.15; p-value 0.009) were associated with HER2-low. HER2-low was associated with worse DFS (HR: 1.32; 95%CI 1.06 − 1.66; p-value 0.015) and OS (HR: 1.42; 95%CI 1.12 − 1.81; p-value 0.004) as compared to HER2 0. No association of HER2-low with DRFS was observed. Conclusions HER2-low is present in more than half of the patients with early ER+ HER2- pure ILCs and is associated with larger tumor size and multifocality. HER2-low is associated with a worse DFS and OS as compared to HER2 0.